Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Dans la langue officielle de son choix : la loi canadienne sur les langues officielles et la notion de « choix » en matière de services publics - Charbonneau, François (Lien social et Politiques, 2011)
L’article s’intéresse à la notion de choix en matière de services publics à la lumière de l’expérience de la notion de « langue de son choix » incluse dans les diverses législations canadiennes depuis plus de quarante ans, c’est-à-dire depuis l’adoption de la Loi sur les langues officielles au Canada. Cet exemple montre bien comment le choix en matière de services publics peut avoir des conséquences délétères non intentionnelles pour les populations les plus vulnérables, dans ce cas-ci, les francophones vivant en situation minoritaire.

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.